H2N2 live attenuated influenza vaccine is safe and immunogenic for healthy adult volunteers - Isakova-Sivak, Irina (Hum Vaccin Immunother, 2015)
H2N2 influenza viruses have not circulated in the human population since 1968, but they are still being regularly detected in the animal reservoir, suggesting their high pandemic potential. To prepare for a possible H2N2 pandemic, a number of H2N2 vaccine candidates have been generated and tested in preclinical and clinical studies. Here we describe the results of a randomized, double-blind placebo-controlled phase 1 clinical trial of an H2N2 live attenuated influenza vaccine (LAIV) candidate prepared from a human influenza virus isolated in 1966. The vaccine candidate was safe and well-tolerated by healthy adults, and did not cause serious adverse events or an increased rate of moderate or severe reactogenicities. The H2N2 vaccine virus was infectious for Humans. It was shed by 78.6% and 74.1% volunteers after the first and second dose, respectively, most probably due to the human origin of the virus. Importantly, no vaccine virus transmission to unvaccinated subjects was detected during the study. We employed multiple immunological tests to ensure the adequate assessment of the H2N2 pandemic LAIV candidate and demonstrated that the majority (92.6%) of the vaccinated subjects responded to the H2N2 LAIV in one or more immunological tests, including 85.2% of subjects with antibody responses and 55.6% volunteers with cell-mediated immune responses. In addition, we observed strong correlation between the H2N2 LAIV virus replication in the upper respiratory tract and the development of antibody responses.